2013
DOI: 10.1039/c3an00560g
|View full text |Cite
|
Sign up to set email alerts
|

A nanosized metal–organic framework of Fe-MIL-88NH2 as a novel peroxidase mimic used for colorimetric detection of glucose

Abstract: In this paper, a nanosized porous metal-organic framework, Fe-MIL-88NH₂, was facilely prepared with a uniform octahedral shape by the addition of acetic acid, and for the first time was demonstrated to possess intrinsic peroxidase-like activity. Kinetic analysis and electron spin resonance measurements indicated that the catalytic behavior was consistent with typical Michaelis-Menten kinetics and follows a ping-pong mechanism. As a novel peroxidase mimic material, Fe-MIL-88NH₂ shows the advantages of high cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(136 citation statements)
references
References 43 publications
(34 reference statements)
7
129
0
Order By: Relevance
“…74-0566). [2][3][4][14][15][16][17] The chargetransfer complexes formed from the one-electron oxidation of TMB by COH could produce two intense characteristica bsorption peaks at 370 and 658 nm. The XRD patterns of HAPNWs and HAP@MIL-100(Fe) NFs with aw ider 2q angle range are shown in FigureS1o ft he Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…74-0566). [2][3][4][14][15][16][17] The chargetransfer complexes formed from the one-electron oxidation of TMB by COH could produce two intense characteristica bsorption peaks at 370 and 658 nm. The XRD patterns of HAPNWs and HAP@MIL-100(Fe) NFs with aw ider 2q angle range are shown in FigureS1o ft he Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…To test the peroxidase-like activity of the HAP@MIL-100(Fe) NFs, we investigatedt he catalytic oxidation of peroxidase substrate 3,3',5,5'-tetramethylbenzidine (TMB) in the presence of [2][3][4][14][15][16][17] The chargetransfer complexes formed from the one-electron oxidation of TMB by COH could produce two intense characteristica bsorption peaks at 370 and 658 nm. [35] The absorbance at 658 nm was monitored to evaluate the optimal catalytic reactionc onditions.…”
Section: Peroxidase-like Activity Of Hap@mil-100(fe) Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal-organic frameworks (MOFs) and MOFs loaded with other catalysts have been reported to exhibit enzyme-like properties [56,57,58,59]. Liu et al reported a nanosized porous metal–organic framework, Fe-MIL-88NH 2 exhibiting intrinsic peroxidase-like activity and used it for colorimetric detection of glucose [59]. Qin et al demonstrated a hemin@metal-organic framework mimicking peroxidase and applied it for glucose detection.…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
“…Prussian Blue, [Fe(III)Fe(II)(CN) 6 ] − , has been also explored to mimic peroxidases. In their earlier study Gu et al showed that a Prussian Blue coating could tune the peroxidase-mimicking activity of γ-Fe 2 O 3 nanoparticles, but later they also found enzyme-like activities of Prussian Blue nanoparticles [58,59]. They also demonstrated that the enzyme-mimicking properties of Prussian Blue nanoparticles were dependent on the microenvironment.…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%